Workplace Spirituality pada Karyawan Koperasi Syariah di Kebumen - Siti Nur Azizah (Universitas Peradaban, 2018)
Workplace spirituality on employee of sharia cooperative in Kebumen, the research that examines spirituality in the workplace, especially in sharia cooperatives, is still small. This study explores the experience of spirituality in the workplace among sharia cooperative employees in Kebumen. The dimensions of spirituality learned include meaningfulness, sense of community and alignment with organizational value. Survey data from 58 sharia cooperative employees revealed that overall employees experienced a high level of spirituality, and employees experienced more work than the sense of community and alignment with organizational value. The result implies that the organization of sharia cooperatives acts as a favorable environment that fosters the experience of spirituality among its employees. Though limited by the mono sectoral nature of this investigation and the eastern context.